Primary cervical hydatid cyst: a rare occurrence - Sultana Nuzhat; Hashim Tariq; Jan Shahida; khan Zahidullah; Malik Tahir; Shah Walayat (BMC, 2012)
Abstract Hydatid disease, a parasitic infection is caused by Echinococcus granulosus. It has serious impact on health and economy especially in countries where it is endemic. It occurs frequently in liver and lung. The disease is chronic and cyst can localize in different organs. A hydatid cyst occurrence in the head and neck is extremely rare. To know the distribution of disease can help in its control and prevention. We report a case of primary cervical hydatid cyst in 20 year old female. A high index of suspicion is required to diagnose hydatid cyst in rare locations like this. Hydatid cyst should be considered in differential diagnosis of benign swellings of head and neck region, so that it can be managed during surgery to prevent acute anaphylaxis. Virtual slides The virtual slides' for this article can be found here: http://www.diagnosticpathology.diagnomx.eu/vs/4915595218376646